Chemogenetic Inhibition of Pain Neurons in a Mouse Model of Osteoarthritis. Issue 7 (2nd June 2017) - Miller, Rachel E.; Ishihara, Shingo; Bhattacharyya, Bula; Delaney, Ada; Menichella, Daniela M.; Miller, Richard J.; Malfait, Anne‐Marie
Abstract : Objective: To determine the ability of drugs that activate inhibitory G protein–coupled receptors (GPCRs) expressed in peripheral voltage‐gated sodium channel 1.8 (NaV 1.8)–positive sensory neurons to control osteoarthritis (OA)–associated pain. Methods: We used designer receptors exclusively activated by a designer drug (DREADD) technology, which employs engineered GPCRs to activate or inhibit neurons upon binding the synthetic ligand clozapine N ‐oxide (CNO). NaV 1.8‐Pdi C57BL/6 mice were generated to express the inhibitory DREADD receptor Pdi in NaV 1.8‐expressing sensory neurons. Destabilization of the medial meniscus (DMM) surgery was performed in 10‐week‐old male mice. Four, 8, 12, or 16 weeks after surgery, knee hyperalgesia or hind paw mechanical allodynia was tested. Subsequently, CNO or vehicle was administered, and the effect on pain‐related behaviors was measured by a blinded observer. Morphine was used as a control. Results: Immunohistochemistry and electrophysiology confirmed functional expression of the inhibitory DREADD receptor Pdi by NaV 1.8‐positive sensory neurons. Acute inhibition of NaV 1.8‐expressing neurons in mice treated with CNO reduced knee hyperalgesia 4 weeks after DMM surgery and reduced mechanical allodynia 8 weeks after DMM surgery. Inhibition had no effect on pain‐related behaviors 12 and 16 weeks after DMM surgery. Morphine, a drug that activates GPCRs in the peripheral and central nervous systems, was still effective in the later stage of experimental OA. Conclusion: Chemogenetic inhibition of NaV 1.8‐expressing neurons blocks knee hyperalgesia and mechanical allodynia in early experimental OA, but is no longer efficacious in the later stages. These data indicate that activation of inhibitory GPCRs located solely outside the central nervous system may be ineffective in treating chronic OA pain.